RADIANCE-HTN SOLO: A MULTICENTER, RANDOMIZED, SHAM-CONTROLLED STUDY OF RENAL DENERVATION IN PATIENTS WITH UNCONTROLLED HYPERTENSION IN THE ABSENCE OF ANTIHYPERTENSIVE MEDICATIONS. (June 2018) - Azizi, M.; Schmieder, R.E.; Mahfoud, F.; Weber, M.; Daemen, J.; Davies, J.; Basile, J.; Kirtane, A.; Wang, Y.; Mauri, L.
Abstract : Objective: The RADIANCE-HTN SOLO trial is the first randomized, double-blind (for endpoint assessors), sham-controlled study of intravascular ultrasound-based renal denervation (RDN) to treat hypertension in an off-medication population that was prospectively powered for efficacy. Design and method: Between March 2016 to December 2017, 804 patients were screened at 44 centers in Europe and the USA. A total of 146 subjects treated with 0–2 antihypertensive medications at screening who had a daytime ambulatory BP > = 135/85 mmHg and < 170/105 mmHg after a 4-week medication washout or run-in period, a suitable renal artery anatomy and eGFR > = 40 ml/min were randomized in a 1:1 ratio to treatment with the Paradise RDN catheter or a sham procedure. The primary endpoint was the between-group difference from baseline to 2 months in daytime ambulatory SBP. Secondary endpoints were difference in changes from baseline to 2 months in daytime ambulatory DBP, 24-hr ambulatory SBP/DBP, and night-time ambulatory SBP/DBP. Patients and clinicians assessing outcomes were blinded to treatment allocation through 6 months. Results: The 146 randomized subjects (42% women; age, 54 ± 10 years) were enrolled in Europe (53%) and in the US (47%). Prior to wash-out, 21%, 41% and 38% of patients were on 0, 1 and 2 medications, respectively. Procedural success rates and 2-month BP results will have been presented prior to this presentation. Predictors of BP response will be presented for this abstract. Conclusions: This is the first prospectively powered randomized, sham-controlled, study of ultrasound-based RDN in hypertensive patients in whom background antihypertensive medications have been withdrawn.